Spectrophotometric Method for Determination of Sulfamethoxazole in Pharmaceutical Preparations by Diazotization-Coupling Reaction - Sinan, Raghad; Al-Uzri, Wasan A (Al-Nahrain Journal of Science, 2011)
A simple, rapid and sensitive spectrophotometric method has been developed for the determination of sulfamethoxazole (SMZ) in pure form and pharmaceutical preparations. The proposed method is based on the diazotization reaction of SMZ with sodium nitrite in hydrochloric acid medium to form diazonium salt, which is coupled with 1-naphthol in sodium hydroxide medium to form azo dye, showing absorption maxima at 525 nm. Linearity was observed from 2–14 μg mL-1 SMZ. Statistical analysis of the results and comparison with results by Bratton-Marshall’s method are also reported.